Combination of Agility and Plyometric Training Provides Similar Training Benefits as Combined Balance and Plyometric Training in Young Soccer Players - Makhlouf, Issam; Chaouachi, Anis; Chaouachi, Mehdi; Ben Othman, Aymen; Granacher, Urs; Behm, David G. (Frontiers in Physiology, 2018)
Introduction: Studies that combined balance and resistance training induced larger performance improvements compared with single mode training. Agility exercises contain more dynamic and sport-specific movements compared with balance training. Thus, the purpose of this study was to contrast the effects of combined balance and plyometric training with combined agility and plyometric training and an active control on physical fitness in youth. Methods: Fifty-seven male soccer players aged (10-12 years) participated in an 8-week training program (2 x week). They were randomly assigned to a balance-plyometric (BPT: n=21), agility-plyometric (APT: n=20) or control group (n=16). Measures included proxies of muscle power (countermovement jump [CMJ], triple-hop-test [THT]), muscle strength (reactive strength index [RSI], maximum voluntary isometric contraction [MVIC] of handgrip, back extensors, knee extensors), agility (4x9-m shuttle run, Illinois agility test with and without the ball), balance (Standing Stork, Y-Balance), and speed (10-30 m sprints). Results: Significant time x group interactions were found for CMJ, hand grip MVIC force, ICODTwithout a ball, agility (4x9 m), standing stork balance, Y-balance, 10 and 30-m sprint. The APT pre- to post-test measures displayed large ES improvements for hand grip MVIC force, ICODT without a ball, agility test, CMJ, standing stork balance test, Y-balance test but only moderate ES improvements with the 10 and 30 m sprints. The BPT group showed small (30 m sprint), moderate (hand grip MVIC, ICODTwithout a ball) and large ES (agility [4x9m] test, CMJ, standing stork balance test, Y-balance) improvements respectively. Conclusion: In conclusion, whereas both groups provided significant improvements, the dynamic balance challenges associated with agility training provided greater ES benefits in 6 of 8 significant measures. It is recommended that youth incorporate balance exercises into their training and progress to agility with their strength and power training.